Analysis of the Muzakki Confidence Index in Paying Zakat in Baitul Mal Regency (BMK) Southeast Aceh - Agara, Andriawan; Alfin, Aidil (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: This study aims to analyze the factors influencing Muzakki's trust in Baitul Mal in Southeast Aceh Regency and identify strategies to enhance trust in zakat payment. Methodology: The research employs a mixed-method approach, combining qualitative and quantitative methods. Primary data was collected, and multiple linear regression analysis was performed using SPSS 26 to evaluate the findings. Results: The study reveals that the Muzakki Confidence Index in Baitul Mal, Southeast Aceh Regency, is 0.88 or 88%, categorized as High Confidence. Despite corruption cases in 2021, trust remains high due to effective management strategies. Findings: The strategies identified to grow Muzakki’s trust include professionalism, transparency, accountability, and credibility in zakat management. Originality: This research highlights the importance of institutional trust in fostering zakat payment in Southeast Aceh and provides actionable strategies for improvement. Novelty: The study integrates trust-building strategies into zakat management and highlights the impact of professionalism and ethical governance.Conclusions: Effective management strategies are essential to maintaining Muzakki’s trust, ensuring optimal zakat collection and distribution. Type of Paper: Empirical research Paper.